G82(P) An assessment of equity in access to local services for looked after children. (24th May 2017) - Keene, J; Mohiddin, A; Wolfe, I
Abstract : Aim: To describe access to services for Looked After Children (LAC) and care leavers from two neighbouring Inner-city Boroughs. Method: We identified care standards for LAC and care leavers through examining NICE and statutory guidance. We compared local practice against those standards by interviewing commissioners and service providers. Results: Housing: 25% of local LAC are housed with foster carers within their own boroughs (England average 58%). The remaining 75% of LAC are spread over 70 different localities, 25% are placed a significant distance away. Any child requiring residential placement must be placed out of area as there is no residential home provision within either borough. Healthcare: There is insufficient capacity within local LAC teams to conduct all annual health assessments for LAC placed in other boroughs, therefore services are heavily reliant on 3 rd party assessments. These services are more costly and their quality is thought to be variable. Access to mental health services is very good for LAC placed locally; however there is no dedicated provision for those not placed locally. Where possible LAC travel back, at their own cost, to access local services. Alternatively they await mainstream services in the locality they are placed. Care leavers: Commissioners identified care leavers as a group in need of additional support services. Local authorities retain responsibility for certain aspects of the wellbeing of LAC when they become care leavers. Consequently all housing is local and 90% of care leavers live in the borough. This change of locality creates additional difficulties for the young people adapting to living independently. Conclusions: Significant inequalities in access to care for LAC and care leavers exist. There is a 2 tier system; LAC placed within the borough have notably better access to services than those placed outside. Ofsted have acknowledged inequalities in access as a national problem; 'local authorities do not have a complete understanding of all the services offered in other localities leading to delays in delivering appropriate care' 1 . More work nationally is required to describe needs of LAC housed out of area, and to shape services accordingly.